Steel structures practical design studies - Al Nageim, H. (Hassan) (Taylor & Francis, 2005)
Contains references to both Eurocodes and British Standards, as well as examples, and sections on sustainability, composite columns and local buckling. This book covers the essentials of structural engineering and structural steel design, and presents an examination of the analysis and design of selected types of structures.